Simulation of Dispersed Pollutant From Incense Burning Within an Enclosed Space - Nguyễn Giáp Thạch; Nguyễn Lữ Phương (Journal of Technical Education Science, 2026)
Indoor air pollution is a serious environmental and public health issue, as modern people spend approximately 80-90% of their time in enclosed spaces. In addition to common emission sources, incense burning – a traditional cultural practice, is a significant source of indoor air pollutants, particularly formaldehyde, but has not received adequate attention. This study focuses on evaluating formaldehyde emissions and dispersion from smoke generated by several commonly used incense types in Viet Nam under different mechanical ventilation conditions. Experiments were conducted in a closed chamber with a volume 1 m3, combined with numerical simulations using the finite volume method implemented in Ansys Fluent to validate and analyze pollutant dispersion. Experimental results showed that, under non-ventilated conditions, the average formaldehyde concentration reached 4.163 mg/m3, approximately four times higher than the short-term exposure limit specified in QCVN 03:2019/BYT. Simulation results obtained using the low-Reynolds-number k-ɛ turbulence model showed good agreement with experimental data, with a deviation of about 5%. The study demonstrates the effectiveness of mechanical ventilation and highlights the applicability of CFD modeling in assessing indoor air pollution.